2022
DOI: 10.3390/cancers14174337
|View full text |Cite
|
Sign up to set email alerts
|

A Score to Predict the Malignancy of a Breast Lesion Based on Different Contrast Enhancement Patterns in Contrast-Enhanced Spectral Mammography

Abstract: Background: To create a predictive score of malignancy of a breast lesion based on the main contrast enhancement features ascertained by contrast-enhanced spectral mammography (CESM). Methods: In this single-centre prospective study, patients with suspicious breast lesions (BIRADS > 3) were enrolled between January 2013 and February 2022. All participants underwent CESM prior to breast biopsy, and eventually surgery. A radiologist with 20 years’ experience in breast imaging evaluated the presence or absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Many studies confirmed the usefulness of CESM in clinical practice, as well as the usefulness of this relatively new diagnostic method [ 8 , 21 , 22 , 23 ]. CESM appears to offer similar diagnostic performance to MRI with the advantage of being cheaper, faster and applicable to more patients (e.g., patients with claustrophobia and pacemakers) [ 24 ].…”
Section: Discussionmentioning
confidence: 92%
“…Many studies confirmed the usefulness of CESM in clinical practice, as well as the usefulness of this relatively new diagnostic method [ 8 , 21 , 22 , 23 ]. CESM appears to offer similar diagnostic performance to MRI with the advantage of being cheaper, faster and applicable to more patients (e.g., patients with claustrophobia and pacemakers) [ 24 ].…”
Section: Discussionmentioning
confidence: 92%
“…1a and c): enhancement was observed, a nodule with suspicious US characteristics (irregular margins, inhomogeneous, vascularized at color Doppler) was highlighted, which was biopsied with US guidance, leading to an invasive ductal carcinoma diagnosis. This is a typical presentation of invasive ductal carcinoma on CEM [11,17]. The patient subsequently underwent mastectomy with sentinel lymph node biopsy.…”
Section: Observations Are As Followsmentioning
confidence: 90%
“…• Screening of high-risk patients with dense breasts is beginning to be considered: CEM appears to demonstrate a superior sensitivity in tumor detection to classical DM and not inferior to tomosynthesis [8,9]. Furthermore, compared with tomosynthesis examinations, preliminary results show that in CEM, the breast is not exposed to a higher average glandular dose [19]. • Surveillance in patients with a prior history of breast cancer: CEM proves to be an excellent tool for use in the surveillance of oncological patients [20].…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, MRI is accepted as the most sensitive imaging technique for detecting and staging breast cancer and is of great help in the study of particularly complex breasts, or of patients with an elevated hereditary–familial risk of developing breast cancer [ 35 ]. With a similar performance to MRI, CESM can also visualize microcalcifications and possibly reduce the rate of false-positive findings and benign biopsies [ 32 , 36 ].…”
Section: Strengths and Limitations Of Current Breast Imaging Techniquesmentioning
confidence: 99%